Sustainable Business of Kopi Kenangan as a Startup Company in Improving the Company's Reputation and Competitiveness - Muharman, Deddy (UPT Publikasi Ilmiah (Universitas Islam Bandung), 2024)
In today's business landscape, sustainability is paramount for long-term success and societal impact. Sustainable business practices provide myriad benefits, including cost savings, productivity enhancement, reputation improvement, and competitiveness. This research investigates the sustainable business model of Kopi Kenangan, a prominent Indonesian startup, and its impact on the company's reputation and competitiveness. Winston (2018) articulates the financial and strategic advantages of sustainability, highlighting cost savings, productivity, reputation enhancement, and global competitiveness. Unsustainable businesses, conversely, face increased operational, reputational, and regulatory risks. This research builds on these findings, examining the correlation between corporate sustainability and investor relations, as noted by Lenox & Meehan III (2014). Kopi Kenangan's journey to unicorn status exemplifies the integration of sustainable practices with business strategy. Achieving a valuation exceeding USD 1 billion, Kopi Kenangan's success underscores the significance of sustainability in attracting investment and fostering growth. Their approach includes responsible ingredient sourcing, eco-friendly packaging, and efforts to minimize environmental impact, reflecting a commitment to the Triple Bottom Line (TBL) framework of profit, people, and planet introduced by Elkington (1994). The qualitative analysis, supported by document studies and expert interviews, reveals that Kopi Kenangan's sustainable business model not only enhances financial performance but also builds strong investor relations and community trust. This research highlights the role of effective communication in fostering investor confidence and sustaining business growth. Kopi Kenangan's practices illustrate the broader benefits of sustainable business: preserving natural resources, reducing pollution, and improving community welfare. Their focus on employee well-being, local community development, and environmental stewardship sets a benchmark for startups aiming to balance profitability with social and environmental responsibility. This study concludes that sustainable business practices are essential for startups to enhance reputation, attract investment, and achieve long-term competitiveness. Kopi Kenangan's success serves as a compelling case for the strategic integration of sustainability in business operations, offering valuable insights for other startups in the F&B sector and beyond.